Founding the Welfare State: Comparative Public Opinion on Taxes and Distribution of Income - Toril Aalberg (Luxembourg Income Study (LIS), 1998)
This paper explores cross-national public perceptions and beliefs about taxes and redistribution of income. Our main concern is whether the welfare regimes and the national tax policies can explain attitudinal variance. Despite our larger database and somewhat different measures, our study array neatly in the line of research, which are not able to declare any significant and systematic policy explanation of variations in public beliefs about taxation. The publics in countries with large tax-loads did not state that they found taxes particularly large, and variation in public perception could not be determined either by welfare regime or tax-rates in the country. Support of progressive taxation did not vary according to how progressive the tax system in the country was. To the contrary, we detected a negative relationship between tax progressivity and support of progressive taxation.
Keywords: 330; Einkommensumverteilung; Steuerpolitik; Welt